Mechanical work and coordinative pattern of cycling: A literature review - Bini, R. R.; Diefenthaeler, F. (Kinesiology, 2009)
In this review paper there three models to calculate mechanical work, the pattern of joint power during steady-state cycling and some theories regarding energy transfer through the joints and coordinative pattern analysis by joint mechanical work distribution will be briefly presented. Finally, there will be a report on the effects of workload, pedalling cadence and saddle height management on joint mechanical work. The first result that emerges from the management of the workload is that the positive mechanical work produced by the joints increases which is mostly related to the concentric muscle contraction. The contribution of hip and knee joints seems to be different from the ankle joint with changes in workload during cycling because the ankle joint muscles should be tuned to optimize stiffness and maximize the effective transmission of mechanical energy to the crank. When changing pedalling cadence, the authors have only agreed with the unchanged contribution of the ankle joint to the total mechanical work, while the hip and knee contribution results differ in the reported research. Lack of evidence in ankle joint function when the resistive force and pedalling cadence relationship are changed during fatigue as the mechanical energy transfer and stiffness function need further research. Controversial results have been reported in the analysis of joint contribution to the total mechanical work for different cycling expertise. Unfortunately, we cannot find conclusive research regarding the effects of saddle height on coordinative pattern mainly based on simultaneous analysis of joint moment distribution, joint kinematics and joint reaction forces.